Ocupaciones humanas en Cabeza de León 1 (Santa Cruz, Argentina) : una aproximación desde la tecnología lítica - Cañete Mastrángelo, Daniela Soledad (2021)
The Patagonian coast has been occupied at least since the Middle Holocene but the way in which humans have interacted with spaces and resources in different areas of the coast has varied. As such, it is important to study the specifics of each occupation. In this paper, the activities that would have taken place at Cabeza de León 1 archaeological site, Monte León National Park, Santa Cruz province, Argentina, are addressed from the study of the recovered lithic assemblages. Results show the use of local raw material, the development of all manufacture stages in situ and the implementation of mainly expedient strategies. It can also be inferred that activities were mostly related to the capture and processing of resources.